2018
DOI: 10.1161/circulationaha.118.034189
|View full text |Cite
|
Sign up to set email alerts
|

Multiprotein Complex With TRPC (Transient Receptor Potential-Canonical) Channel, PDE1C (Phosphodiesterase 1C), and A2R (Adenosine A2 Receptor) Plays a Critical Role in Regulating Cardiomyocyte cAMP and Survival

Abstract: We have characterized a novel multiprotein complex comprised of AR, PDE1C, and TRPC3, in which PDE1C is activated by TRPC3-derived Ca, thereby antagonizing AR-cAMP signaling and promoting cardiomyocyte death/apoptosis. Targeting these molecules individually or in combination may represent a compelling therapeutic strategy for potentiating cardiomyocyte survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Immuno-histochemistry localizes A 2B R at mitochondria 45 and it is also expressed in vascular tissue and fibroblasts where it regulates proliferation, vascular tone, and anti-fibrotic signaling 46 . PDE1 inhibition is also antifibrotic 47 , regulates smooth muscle proliferation 48 , and as shown by Zhang et al 49 , also protects against doxorubicin-induced myocyte apoptosis in vitro and in vivo . In this study, they found PDE1 co-localizes with A 2 R in a membrane macromolecular complex overlapping t-tubules, and that both A 2A R and A 2B R blockade prevents the anti-apoptotic efficacy from PDE1 inhibition.…”
Section: Discussionmentioning
confidence: 82%
“…Immuno-histochemistry localizes A 2B R at mitochondria 45 and it is also expressed in vascular tissue and fibroblasts where it regulates proliferation, vascular tone, and anti-fibrotic signaling 46 . PDE1 inhibition is also antifibrotic 47 , regulates smooth muscle proliferation 48 , and as shown by Zhang et al 49 , also protects against doxorubicin-induced myocyte apoptosis in vitro and in vivo . In this study, they found PDE1 co-localizes with A 2 R in a membrane macromolecular complex overlapping t-tubules, and that both A 2A R and A 2B R blockade prevents the anti-apoptotic efficacy from PDE1 inhibition.…”
Section: Discussionmentioning
confidence: 82%
“…The anti-apoptotic effects of PDE1C deficiency or inhibition were mediated by the cAMP/PKA axis ( 18 ). Zhang et al ( 25 ) further demonstrated that PDE1C colocalized with adenosine A2 receptors (A 2 Rs) in cardiomyocyte membrane and T-tubules and that the anti-apoptotic effect of PDE1 inhibition is dependent on cAMP-generating A 2 Rs in cardiomyocytes, suggesting that PDE1C selectively regulates A 2 R/cAMP signaling in cardiomyocytes. Since impaired PQC resulting from PFI is sufficient to cause cardiomyocytes to die, proteasome enhancement may also contribute to the prosurvival effect of PDE1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in tissues, PDE1C can degrade cyclic AMP, which conducts several subcellular functions that result in positive inotropic and lusitropic effects [3]. Recent studies have demonstrated that PDE1C is an important regulator of cardiac cAMP signaling and has a direct role in cardiomyocyte death/apoptosis [7,36]. Emerging studies suggest that it may be an important candidate for therapeutic targeting in heart failure [7,37].…”
Section: Discussionmentioning
confidence: 99%